The female stage direction (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
In the field of puppet theater in Argentina, the female presence was and is very important. All this enormous work of women in the art of puppets was not exempt, as nothing is, from the patriarchal gaze on the initiators of our language. This article reflects on the legitimacy, recognition and aesthetic diversity of the work done by women and wonders if there is a direction that we can call feminine in the field of puppet and object theatre.